Lessons for Managing Lake Basins for Sustainable Use - World Bank (Washington, DC, 2012)
The objective of this economic and sector work (ESW) is to distill and extend those findings from the GEF Medium Sized Project (MSP) implemented by the World Bank entitled Towards a Lake Basin Management Initiative: Sharing Experiences and Lessons from GEF and Non-GEF Lake Basin Management Projects that are relevant to the GEF and development partners, by extending the types of monitoring and evaluation (M&E) indicators-process, stress reduction, and environmental status-previously developed by the GEF for international waters projects. Twenty-eight lakes were studied in the MSP. While this ESW outlines the environmental status of the lakes in the MSP study and the stress reduction activities undertaken at these lakes, the main focus of this ESW is on the process indicators, which measure the development of an enabling environment for lake management.